The Role of Gut Microbiota and Probiotics in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Leong, Xue Bin; Tang, Chuan Zhe; Lee, Chloe Zi Ying; Lee, Zoe Ling Hui; Koo, Thai Hau (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Probiotics have emerged as a promising treatment for inflammatory bowel diseases (IBD). Moreover, the efficacy and safety of gut microbiota should be comprehensively studied. This systematic review and meta-analysis aim to study randomized controlled trials (RCTs) of IBD patients using probiotics, compared to conventional drugs or placebo. Eligible RCTs involving adult IBD patients were identified using MEDLINE, EMBASE, and the Cochrane Controlled Trials Register until May 2024. Fixed-effects modeling was used to calculate risk ratio (RRs) with 95% confidence intervals (CIs) based on adverse event data due to low-moderate heterogeneity. The search yielded 2392 articles, including seven RCTs that met the criteria. On the other hand, concerning effectiveness outcomes, probiotics had an overall RR of 1.52 (95% CI: 1.08–2.13, p=0.02) compared to the controls. The comparable risk was demonstrated by the overall RR of 1.05 (95% CI: 0.59–1.86, p=0.87), which showed no apparent difference in the rate of adverse events between the groups on probiotics and the control group. Three studies were not included because their RR was non-estimable. Nevertheless, these three studies upheld the safety and tolerability of the probiotics. Though the number is small, and despite differences in types and schedules of probiotics, it can be suggested that probiotics enhance therapy responses in IBD patients. Further research with larger sample sizes and a broader range of demographics is necessary to shed more light on the effectiveness of probiotics.